Toward an alternative approach for the preparation of low-temperature titanium dioxide blocking underlayers for perovskite solar cells. Issue 17 (10th April 2019) - Aung, Su Htike; Zhao, Lichen; Nonomura, Kazuteru; Oo, Than Zaw; Zakeeruddin, Shaik M.; Vlachopoulos, Nick; Sloboda, Tamara; Svanström, Sebastian; Cappel, Ute B.; Hagfeldt, Anders; Grätzel, Michael
Abstract : The anodic electrodeposition method is investigated as an alternative technique for the preparation of a titanium oxide blocking underlayer for perovskite solar cells. Abstract : The anodic electrodeposition method is investigated as an alternative technique for the preparation of a titanium oxide (TiO2 ) blocking underlayer (UL) for perovskite solar cells (PSCs). Extremely thin Ti IV -based films are grown from aqueous acidic titanium(iii ) chloride in an electrochemical cell at room temperature. This precursor layer is converted to the UL (ED-UL), in a suitable state for PSC applications, by undertaking a sintering step at 450 °C for half an hour. PSCs with the composition of the light-absorbing material FA0.85 MA0.10 Cs0.05 Pb(I0.87 Br0.13 )3 (FA and MA denote the formamidinium and methylammonium cations, respectively) based on the ED-UL are compared with PSCs with the UL of a standard type prepared by the spray-pyrolysis method at 450 °C from titanium diisopropoxide bis(acetylacetonate) (SP-UL). We obtain power conversion efficiencies (PCEs) of over 20% for mesoscopic perovskite devices employing both ED-ULs and SP-ULs. Slightly higher fill factor values are observed for ED-UL-based devices. In addition, ED-ULs prepared by the same method have also been applied in planar PSCs, resulting in a PCE exceeding 17%, which is comparable to that for similar PSCs with an SP-UL. The preparation of ED-ULs with a lower sintering temperature, 150 °C, has also been examined. The efficiency of a planar PSC incorporating this underlayer was 14%. These results point out to the possibility of applying ED-ULs in flexible planar PSCs in the future.